RELATIONSHIP BETWEEN INVESTMENTS IN INTELLECTUAL CAPITAL AND TOTAL BOOK VALUE - Petković, Miloš; Djordjević, Milica (The European Journal of Applied Economics, 2023)
The research paper aims to empirically investigate the relationship between investments in intellectual capital and French pharmaceutical companies’ total book value. The multiple statistical regression analyses were done on 36 companies in the period from 2008 until 2016. The research models investigate the transformation process from expenses into concrete assets accepted and recognized by international accounting standards. The investments in structural capital component of intellectual capital influence negatively, with a coefficient of -0.00374. On the other side, investments in human capital  and external capital compoments influence positively, with its coefficients 0.861388 and 0.077 respectively. The sample size, as well as the lack of available financial information related to the research and development (R&D) and marketing expenses disclosed in the company’s accounts, are two main limitations of the paper. These results prove that French pharmaceutical companies transform their long-term intellectual capital investments into asset value.
Keywords: investments in intellectual capital; total book value; pharmaceutical companies; France